Ambient Storage Derived Surface Contamination of NCM811 and NCM111: Performance Implications and Mitigation Strategies. Issue 12 (2nd July 2019) - Sicklinger, Johannes; Metzger, Michael; Beyer, Hans; Pritzl, Daniel; Gasteiger, Hubert A.
Abstract : The quality of metal oxide-based battery active materials is compromised by surface contamination from storage and handling at ambient conditions. We present a detailed analysis of the true nature and the quantity of the surface contaminants on two different cathode active materials, the widely used LiNi1/3 Co1/3 Mn1/3 O2 (NCM111) and the Ni-rich LiNi0.8 Co0.1 Mn0.1 O2 (NCM811). We process these materials in three distinct conditions "wet" (excessive exposure to moisture), "dry" (standard drying of as-received materials), and "calcined" (heat-treatment of cathode powders). Surface contaminants are then quantified by thermogravimetric analysis coupled with mass spectrometry (TGA-MS), and their reactivity with an ethylene carbonate-based electrolyte is evaluated using on-line mass spectrometry (OMS). We demonstrate that not only the commonly assumed LiOH and Li2 CO3 residues account for NCM performance deterioration upon storage in moisture and CO2 containing atmosphere, but also basic transition metal hydroxides/carbonates formed on the material surface. Eventually, we showcase a thermal treatment that removes these transition metal based surface contaminants and leads to superior cycling stability.